THE RELATIONSHIP OF SELF-CONTROL AND CONFORMITY WITH CONSUMPTIVE BEHAVIOR OF NETWORK COMPUTER ENGINEERING STUDENTS AT SMK NEGERI 2 BINJAI - Lahmuddin Lubis; Abdillah Abdillah; Husni Khaidirali Lubis (State Islamic University of North Sumatra Indonesia, 2020)
The purpose of this study was to determine: 1) The Relationship of Self-control with Consumptive Behavior of Computer Network Engineering students at SMK Negeri 2 Binjai; 2) Relationship between Conformity and Consumptive Behavior of Network Computer Engineering students at SMK Negeri 2 Binjai; and 3) Relationship between Self-control and Conformity with Consumptive Behavior of Network Computer Engineering students at SMK Negeri 2 Binjai. This study uses correlational quantitative research that aims to determine the relationship between self-control and conformity with students' consumptive behavior. The sampling technique used is cluster technique. random sampling. The cluster random sampling technique is to randomize groups, not individual subjects. Data collection uses psychological measurement scales. As a measurement tool, a psychological scale has special characteristics that distinguish it from various other forms of data collection tools, such as questionnaires, questionnaires, inventory, and others. Data analysis technique used is to use a hypothesis test, F-Test, T-Test and Multiple Regression. This study found that: 1) There is a significant relationship between the relationship of self-control with consumptive behavior, the relationship of self-control with consumptive behavior depends on the level of self-control owned; 2) There is a relationship between conformity with consumptive behavior. The relationship between conformity and consumptive behavior here is in terms of buying and consuming behavior; and 3) There is a relationship between self-control and conformity with consumptive behavior, the relationship between self-control and conformity with consumptive behavior here if the level of self-control possessed by a teenager is high, a condition occurs where a person can always control himself so that he can control himself from various desires that are too overwhelming and excessive. Keywords: Self-control, Conformity, Consumptive